Perlakuan Cairan Nutrisi AB Mix terhadap Tanaman Pakcoy (Brassica rapa L.) Hidroponik - Aidil Fitri, Siti Nurul; Monica, Abel; Safitri, Alia; Tua Sitinjak, Rizky Hot; Putri, Jenika (Seminar Nasional Lahan Suboptimal, 2024)
Fitri, S. N. A., Monica, A., Safitri, A, Putri, J., & Sitinjak, R. H. T. (2024). AB mix nutrient salution treatment for hydroponic pakchoy (Brassica rapa L) plants. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 156–163). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The demand for pakcoy vegetables among the public is increasing because people are starting to realize their nutritional needs, but in Indonesia the amount of agricultural land per capita is still relatively low. The purpose of this observation is to find out how many ml of AB Mix nutrition is appropriate for pakcoy (Brassica rapa L) plants. The observation method used a Randomized Block Design with each treatment repeated three times. The system used in this observation is a wick hydroponic system.In the first observation, the plants did not show too much change. In the second observation, plant height, number of leaves, and symptoms began to show changes because the plants had absorbed enough nutrients or absorbed excessive nutrients. In the third observation the plants experienced many changes, one of which was the 220 ml dose treatment, the plants died because they absorbed too many nutrients, and experienced toxicity.Different dose treatments will make plant height, and the number of leaves, increase or wilt, even die. The highest observed pakcoy plant height in 3 observations was 18 cm, the number of leaves observed in 3 observations was 11 leaves at most, while for symptoms, at a dose of 220 ml the most severe symptoms, namely experiencing toxicity due to excess nutrients absorbed by plants causing pakcoy plants to die.The best nutrition for pakcoy plants is 110 ml, giving the right dose will affect the development of these plants, such as plant height, number of leaves, or symptoms that appear when lacking or excess nutrients.